2020
DOI: 10.1111/ele.13669
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic structure of plant facilitation networks

Abstract: Identifying the plant traits that determine the outcome of facilitation interactions is essential to understand how communities are assembled and can be restored. Plant facilitation networks are phylogenetically structured but which traits are behind such a pattern is unknown. We sampled plant interactions in stressful ecosystems from south‐eastern Spain to build seedling and adult facilitation networks. We collected 20 morphological and ecophysiological traits for 151 species involved in interactions between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 60 publications
0
14
1
Order By: Relevance
“…Under drought stress, plants might facilitate the growth of neighbouring plants by increasing soil moisture through hydraulic lift or providing shade, hence reducing evapotranspiration (Maestre et al., 2009 ). As such, nurse plants are expected to be shrubs, subshrubs and other large perennials with a large spread and deep root systems (Navarro‐Cano et al., 2021 ; Schöb et al., 2013 ). The two non‐sensitive shrub species included in this analysis, Thymus praecox and Thymus pulegioides , had positive shifts in their associations with more than half of the drought‐sensitive species (60% and 56%, respectively), which might indicate facilitation under drought by these species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under drought stress, plants might facilitate the growth of neighbouring plants by increasing soil moisture through hydraulic lift or providing shade, hence reducing evapotranspiration (Maestre et al., 2009 ). As such, nurse plants are expected to be shrubs, subshrubs and other large perennials with a large spread and deep root systems (Navarro‐Cano et al., 2021 ; Schöb et al., 2013 ). The two non‐sensitive shrub species included in this analysis, Thymus praecox and Thymus pulegioides , had positive shifts in their associations with more than half of the drought‐sensitive species (60% and 56%, respectively), which might indicate facilitation under drought by these species.…”
Section: Discussionmentioning
confidence: 99%
“…For example, rather than acting as a nurse, the graminoid Bromus erectus (49% positive shifts with drought‐sensitive species) might have benefitted from reduced competition with increasing drought (Liancourt et al., 2005 ). Additionally, interactions also depend on the traits of the facilitated species and the similarity of traits of the interacting species, because nurses generally facilitate species with traits different from their own (He et al., 2013 ; Navarro‐Cano et al., 2021 ). Lastly, this picture is complicated further by the plasticity of these plant traits to plant fitness and life stage.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of plant functional traits within a community has been increasingly used to infer the processes that govern plant community assembly ( Westoby and Wright 2006 ; Kraft and Ackerly 2014 ; Xu et al 2018 ; Navarro-Cano et al 2021 ), including those mediated by pollinator-mediated interactions (e.g. Sargent and Ackerly 2008 ; McEwen and Vamosi 2010 ; de Jager et al 2011 ; Wolowski et al 2017 ; Bergamo et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is somewhat surprising that these asymmetries, and their role in community assembly, have not been more often considered when evaluating community-wide consequences of pollinator-mediated interactions. For instance, recent studies that have evaluated the role of phenotypic traits in determining the outcome of community-wide species interactions have also suggested that both, competition and facilitation, likely play a role in the assembly of plant communities ( Tur et al 2016 ; Bergamo et al 2018 ; Navarro-Cano et al 2021 ; Wei et al 2021 ). Although the importance of the interplay between competition and facilitation in the assembly of co-flowering communities was proposed more than 35 years ago ( Rathcke 1983 ; Mitchell et al 2009 ), only few studies have experimentally evaluated the bidirectionality of pollinator-mediated interactions between co-flowering species (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…& Sandwith. These species in turn facilitate the recruitment of several species of the Tetraclinis forest underneath their canopies [36].…”
Section: Study Areamentioning
confidence: 99%